2018
DOI: 10.3389/fimmu.2018.00688
|View full text |Cite
|
Sign up to set email alerts
|

miR-466a Targeting of TGF-β2 Contributes to FoxP3+ Regulatory T Cell Differentiation in a Murine Model of Allogeneic Transplantation

Abstract: The promise of inducing immunological tolerance through regulatory T cell (Treg) control of effector T cell function is crucial for developing future therapeutic strategies to treat allograft rejection as well as inflammatory autoimmune diseases. In the current study, we used murine allograft rejection as a model to identify microRNA (miRNA) regulation of Treg differentiation from naïve CD4 cells. We performed miRNA expression array in CD4+ T cells in the draining lymph node (dLN) of mice which received syngen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…U6, SnorD96, Snor68, Snor234, and Snor202 were evaluated for stability among groups and SnorD96 was chosen for normalization. SnorD96 has also been used by others[ 39 , 40 ]. Primers were purchased from Qiagen, Maryland.…”
Section: Methodsmentioning
confidence: 99%
“…U6, SnorD96, Snor68, Snor234, and Snor202 were evaluated for stability among groups and SnorD96 was chosen for normalization. SnorD96 has also been used by others[ 39 , 40 ]. Primers were purchased from Qiagen, Maryland.…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow derived macrophages (BMDM) were generated by isolating bone marrow cells from the tibia and femur of 6–8 week old naïve female C57Bl6/J mice and culturing in complete DMEM/F12 medium supplemented with 10% heat-inactivated FBS, 1% penicillin/streptomycin, 2 mM L-glutamine, and 1U/mL macrophage-colony stimulating factor (M-CSF, Biolegend 576406) for 7 days as previously described (21). Lymphocytes from mesenteric, inguinal, axillary, and cervical lymph nodes were isolated from naïve 6–8 week old female C57Bl6/J mice as previously described (34). Day 7 BMDM were re-plated in complete RPMI 1640 medium supplemented with 10% heat-inactivated FBS, 1% penicillin/streptomycin, 2 mM L-glutamine, 10 mM HEPES buffer, and 0.0002% β-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Micro466a-3p. Becker et al analysed the microRNA expression profile of CD4 + T cells from the draining lymph node of a murine model of allogenic transplantation and found that micro466a-3p expression was increased after allogeneic transplantation [71]. To further research the role of micro466a-3p in Treg, micro466a-3p was transfected into CD4 + T cells, which could reduce iTregs, while inhibiting micro446-3p expression in CD4 + T cells could increase Tregs and reduce effector cells.…”
Section: Micro146amentioning
confidence: 99%